THE DEVELOPMENT OF LEGAL AND MORAL RELATION THOUGHTS AND ITS IMPLEMENTATION TO INDONESIAN LEGISLATION SYSTEM - Arnanda Yusliwidaka; Muhammad Ardhi Razaq Abqa; Satrio Ageng Rihardi (Universitas Tidar, 2022)
This research discusses the development of legal and moral relation that is inseparable from two very influential thoughts (mahzab): natural law and legal positivism. The views of both thoughts are in contradiction with each other on legal and moral relations. Natural legal thought explains that law and moral are interrelated and even interdependent, while legal positivism thought views that law and moral are two different and non-interconnected things. The objective of research is to study the development of relation between law and moral in Indonesian legislation system. The research method used was juridical normative method using primary and secondary law material inventoried to get prescriptive legal analysis. The result of research shows that legal and moral relation in Indonesian legislation system, by seeing the relation at substance level indicating integrative relation and at structural level indicating independent relation. In the relation, it can be understood that legal and moral relation is interconnected on the one hand and not interconnected in its law enforcement aspect on the other hand. Thus, the recommendation in this research is that legal substance and legal structure elements should complement each other as an intact legal system, to actually give law certainty, justice, and benefit to the people.